Design of an additively manufactured thermal solution for an axial flux switched reluctance motor - Martin Sarap; Shalini Singh; Ants Kallaste; Ahmed Qureshi; Hans Tiismus; Toomas Vaimann; Payam Shams Ghahfarokhi (Case Studies in Thermal Engineering)
This study presents the design and evaluation of an additively manufactured thermal solution for an axial flux switched reluctance motor, aimed at enhancing its applicability in light unmanned aircraft propulsion. The primary objective is to optimize the motor's power-to-weight ratio by improving its thermal management through innovative heatsink designs. The methodology involves a comprehensive design procedure to dimension a conventional finned heatsink. The performance of the heatsink is experimentally tested under practical conditions using a motorette setup and cooling fans. Key findings indicate that the proposed thermal solution can enable very high current densities for an air-cooled electrical machine.